The Production, Transportation, and Performance of Physicians, Nurses, and Midwives in Indonesia : An Update - Anderson, Ian; Meliala, Andreasta; Marzoeki, Puti; Pambudi, Eko (World Bank Group, Washington, DC, 2014)
Indonesia launched the national health insurance program - Jaminan Kesehatan National (JKN), on January 1, 2014, and aims to achieve universal health coverage (UHC) by 2019. Achieving UHC means not only increasing the number of people covered but also expanding the benefits package and ensuring financial protection. Although the JKN benefits package is comprehensive, a key challenge related to the capacity to deliver the promised services is ensuring the availability, distribution, and quality of human resources for health (HRH). Of Indonesia's 33 provinces, 29 do not have the WHO recommended ratio of 1 physician per 1,000 population, although Indonesia regularly produces 6,000 to 7,000 new physicians annually. The shortage of nurses in hospitals and health centers (puskesmas) is noticeable despite the large number of graduates. The government's health worker contract policy (PTT [Pegawai Tidak Tetap]) was the main policy lever to improve the distribution of physicians and midwives; it offered a shorter contract and higher monetary benefits for rural and remote postings. Nevertheless, evolution of the policy over more than two decades of implementation indicates that the outcome has not been totally satisfactory and that distribution problems remain. Physician maldistribution has been particularly affected by the number and concentration of hospitals in urban areas, as well as by government's policy of allowing dual practice. Aside from HRH production and distribution figures, key information on the quality of Indonesian physicians, nurses, and midwives is limited. The latest data from the 2007 Indonesia Family Life Survey (IFLS) vignettes, which measured diagnostic and treatment ability, showed low average scores across these three integral health worker categories. Indonesia is addressing the quality issue by improving the quality assurance system of health professional education through school accreditation and graduate certification and by strengthening health professional registration and recertification systems. With these issues in mind, if Indonesia is to attain UHC by 2019, significant and concerted effort to improve the availability, distribution, and quality of human resources for health is required.